RNA-protein cross-linking in Escherichia coli 30S ribosomal subunits; determination of sites on 16S RNA that are cross-linked to proteins S3, S4, S7, S9, S10, S11, S17, S18 and S21 by treatment with bis-(2-chloroethyl)-methylamine. - Greuer, B (1987)
RNA-protein cross-links were introduced into E. coli 30S ribosomal subunits by treatment with bis-(2-chloroethyl)-methylamine. After partial nuclease digestion of the RNA moiety, a number of cross-linked RNA-protein complexes were isolated by a new three-step procedure. Protein and RNA analysis of the individual complexes gave the following results: proteins S4 and S9 are cross-linked to the 16S RNA at positions 413 and 954, respectively. Proteins S11 and S21 are both cross-linked to the RNA within an oligonucleotide encompassing positions 693-697, and proteins S17, S10, S3 and S7 are cross-linked within oligonucleotides encompassing positions 278-280, 1139-1144, 1155-1158, and 1531-1542, respectively. A cross-link to protein S18 was found by a process of elimination to lie between positions 845 and 851.